TANTANGAN GURU SEKOLAH LUAR BIASA PADA PEMBELAJARAN IPA DI ABAD 21 - Salamah Agung; Arini Nurhidayah Khoirunisa; Siti Suryaningsih (ALOTROP, 2022)
This study is aimed at finding out the challenges faced by teachers of students with special needs in science learning for the 21st century. This study uses descriptive methods with a case study approach. Data analysis in this study included data reduction (data reduction), data presentation (data display) and drawing conclusions or verification (conclusion drawing/verification). The results of this study indicate that facing the 21st century teachers are challenged with the need to acquire several abilities, such as, 1) communicate fluently in sign language, 2) explain clearly the science concept and its relationship with other concepts, 3) build a classroom atmosphere with class discussions, 4) conduct different teaching, 5) build realistic expectations, 6) build student experience through experiments, 7) increase access to information, 8) discipline of time. In general, the teachers must be able to apply scientific skills, and must fulfill the four 21st century competencies, namely, critical thinking/problem solving, communication, collaboration, and creativity/innovation.Keywords: School with Special Needs, Science Learning faces the 21st century, 21st Century Teacher Challenges